2009
DOI: 10.3747/co.v16i2.420
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Chemotherapy: Changing the Paradigm That More Is Better

Abstract: The introduction of the “maximum tolerated dose” in usual treatment protocols (and its concomitant overt toxicity) made necessary the imposition of rest periods between cycles of therapy—a practice that not only involves re-growth of tumour cells, but also growth of selected clones resistant to the therapy. To avoid the problems caused by traditional chemotherapeutic regimens, a new modality of drug administration called “metronomic chemotherapy” has been proposed. This name makes reference to the chronic, equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 70 publications
3
113
0
2
Order By: Relevance
“…The rationale of this combination is derived from preclinical models where cytotoxic drugs like etoposide and cyclophosphamide, administered on metronomic modality, with short and regular inter-cycle intervals, chronically and generally at low doses, 15 showed cytotoxic activity on activated endothelial cells (anti-angiogenic activity), immunosuppressive blood cell populations like immunoregulatory T lymphocytes (with a CD4 + CD25 + FoxP3 + immunophenotype) and immunosuppressive myeloid precursors (immuno-modulating activity). These drugs given with dose/dense schedules became additionally able to force cancer cells to acquire a less aggressive phenotype (epigenetic effect).…”
Section: Resultsmentioning
confidence: 99%
“…The rationale of this combination is derived from preclinical models where cytotoxic drugs like etoposide and cyclophosphamide, administered on metronomic modality, with short and regular inter-cycle intervals, chronically and generally at low doses, 15 showed cytotoxic activity on activated endothelial cells (anti-angiogenic activity), immunosuppressive blood cell populations like immunoregulatory T lymphocytes (with a CD4 + CD25 + FoxP3 + immunophenotype) and immunosuppressive myeloid precursors (immuno-modulating activity). These drugs given with dose/dense schedules became additionally able to force cancer cells to acquire a less aggressive phenotype (epigenetic effect).…”
Section: Resultsmentioning
confidence: 99%
“…Continuous administration of the drug in low doses also lessens tumour angiogenesis and inhibits circulating endothelial progenitor cells 23 . Thus, metronomic chemotherapy could be good choice in certain cancer types and in selected patients, as well as in some combination or maintenance therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II trial of bevacizumab and dose/dense chemotherapy with cisplatin and metronomic daily oral etoposide in advanced non-small-cell-lung cancer patients [21][22][23][24][25][26][27] Our study was also based on the results of a previous phase II trial which showed the low level of toxicity and the antitumor activity of a metronomic chemotherapy doublet with cisplatin and daily oral etoposide (mPE regimen) in patients with high risk advanced NSCLC. 27 The results of the previous phase I mPEBev trial provided preliminary evidence of antitumor activity in advanced NSCLC including squamous cell histology; additionally, they allowed the identification of the most active biological dose (MABD) and the maximal tolerated dose (MTD) of bevacizumab within the mPEBev regimen, in a range between 5 and 7.5 mg/kg, to be used for further studies.…”
Section: Introductionmentioning
confidence: 99%